E-158 Trends in elective treatment strategies for brain aneurysms. (23rd July 2022) - Lauzier, D; Cler, S; Jayaraman, K; Osbun, J; Chatterjee, A; Moran, C; Kansagra, A
Abstract : Introduction: Elective treatment of intracranial aneurysms comprises a large share of neurointerventional practice, with a proliferation of new devices contributing to the tremendous growth of this area. Traditionally, endovascular treatment of intracranial aneurysms was limited to coiling and coiling with adjunct strategies. However, the development of flow-diverting stents such as Pipeline and endosaccular devices such as Woven endobridge (WEB) have diversified the treatment options for these aneurysms. Here, we review elective endovascular brain aneurysm treatments over time at a high-volume neurointerventional center. Methods: Clinical data and device type for elective aneurysms treatments were retrospectively obtained from a high-volume center from 2002 to 2021. Treatment types recorded included coiling, balloon-assisted coiling, flow diversion, liquid embolization, parent vessel sacrifice, stent-assisted coiling, stent-assisted coiling with an X or Y configuration, and WEB. Gross trends from initial years of analysis were compared to 2019 due to the limitation of elective cases in 2020 due to the ongoing pandemic and an incomplete data set for 2021 due to the timing of data collection. Clinical data and device type for elective aneurysms treatments were retrospectively obtained from a high-volume center from 2002 to 2021. Treatment types recorded included coiling, balloon-assisted coiling, flow diversion, liquid embolization, parent vessel sacrifice, stent-assisted coiling, stent-assisted coiling with an X or Y configuration, and WEB. Gross trends from initial years of analysis were compared to 2019 due to the limitation of elective cases in 2020 due to the ongoing pandemic and an incomplete data set for 2021 due to the timing of data collection. Results: In total, 1329 elective aneurysm treatments performed were available for review in the study period. In 2002, 82% of aneurysms were treated with coiling, 13% with balloon coiling, and 5% with parent vessel sacrifice. In 2019, 47% of aneurysms were treated with flow diversion, 17% with stent-assisted coiling, 16% with WEB, and 15% with coiling. Complete overall trends and counts over time are demonstrated in Figure 1 . Conclusions: Our data demonstrates an expected trend of increased flow diversion and endosaccular device use as these treatment options became readily available over time. The availability of these treatments have led to standalone coiling being less frequently pursued. Disclosures: D. Lauzier: None. S. Cler: None. K. Jayaraman: None. J. Osbun: 2; C; Medtronic, Microvention. A. Chatterjee: None. C. Moran: 2; C; Medtronic, Cerenovus, Microvention, Stryker, Balt. A. Kansagra: 2; C; Microvention, Penumbra.